PEACEFUL UNDERGROUND NUCLEAR EXPLOSIONS: CURRENT ISSUES ON RADIATION SAFETY FOR GENERAL PUBLIC - V. P. Ramzaev; V. S. Repin; E. V. Khramtsov (Радиационная гигиена, 2016)
The paper contains brief summary of original and published radiological data relevant to the sites of peaceful underground nuclear explosions: «Globus-1»,«Dnepr-1,2», «Crystal», «Kraton-3», «Kraton-1», «Kimberlit-1», «Angara», «Quartz-3», «Benzol».The criteria for the guaranties of radiation safety for general public are considered.